2015
DOI: 10.1007/s13592-015-0390-x
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype diversity and genetic similarity among populations of the Eastern honey bee from Himalaya-Southwest China and Nepal (Hymenoptera: Apidae)

Abstract: -Apis cerana Fabricius, the principle mainland species of Apis s.str. in Asia, remains an amalgamation of populations with considerable variation and regionally specialized morphotypes. In this study, populations of A. cerana were evaluated from the Himalayan region and areas in southwestern China as well as from neighboring Nepal based on a 97-bp-long fragment of mtDNA spanning the COI and COII genes. A total of 14 haplotypes were detected among the 58 sampled sequences, including 11 new haplotypes and 3 hapl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…2000 ; Tan et al. 2006 , 2007 , 2015 ; Zhao et al. 2014 ); however, these studies only provided limited information about A. cerana due to the short fragment of A. cerana tRNAleu-COII.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2000 ; Tan et al. 2006 , 2007 , 2015 ; Zhao et al. 2014 ); however, these studies only provided limited information about A. cerana due to the short fragment of A. cerana tRNAleu-COII.…”
Section: Discussionmentioning
confidence: 99%
“…2000 ; Radloff et al. 2010 ; Hepburn and Radloff 2011 ; Tan et al. 2015 and references therein), knowledge of the evolution and adaptation of A. cerana is limited due to the lack of the studies at the genomic level.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, our study has demonstrated that bees from Cuba have a smaller body size than those from Costa Rica, since the eight morphometric characters evaluated resulted with significant differences. Morphometric differences in body size are possibly an adaptive response to the local environment, as observed in several insect groups (Arnett and Gotelli 1999;Stillwell et al 2007;Abbasi et al 2009) and other stingless bee species (Rinderer et al 1991;Batalha-Filho et al 2010;Tan et al 2016). Despite the observed variation in some morphometric traits of the stingless bee populations of M. beecheii from Cuba and Yucatán, the base of the morphometric structure of the species is still maintained.…”
Section: Discussionmentioning
confidence: 98%
“…While the western honey bee has been introduced throughout the Varroa native range, mitochondrial data, which are geographically informative (Figure 1), suggest that switches occurred only in Korea, Japan and the Philippines (V. destructor) and Papua New Guinea (V. jacobsoni) (3,10,11). A. cerana subspecies are strongly differentiated geographically (35)(36)(37)(38)(39), and Varroa mitotypes mirror host biogeography and subspecies distribution (9,11,40). This suggests that Varroa populations may vary in traits, such as host specificity, as a result of their previous coevolutionary interaction with local A. cerana subspecies.…”
Section: Discussionmentioning
confidence: 99%
“…While the western honey bee has been introduced throughout the Varroa native range, mitochondrial data, which are geographically informative (Figure 1), suggest that switches occurred only in Korea, Japan, Philippines ( V. destructor ), Papua New Guinea and possibly Thailand ( V. jacobsoni ) (Roberts, Anderson, and Tay 2015; Navajas et al 2010; Beaurepaire et al 2015; Dietemann et al 2019). A. cerana subspecies are strongly differentiated geographically (Radloff et al 2010; K. Tan et al 2016; Chen et al 2018; Yancan et al 2019; Ilyasov et al 2019; Ji et al 2020), and Varroa mitotypes mirror host biogeography and subspecies distribution (Warrit, Smith, and Lekprayoon 2006; Beaurepaire et al 2015; Rueppell et al 2011; Dietemann et al 2019).…”
Section: Discussionmentioning
confidence: 99%